Ein "leidenschaftlicher Gott": zu einem zentralen Motiv biblischer Theologie - Markl, Dominik (Zeitschrift für katholische Theologie, 2015)
One of the most pervading motifs in OT literature is that of God being spoken of as a jealous God. This article ask the question of the meaning of calling God jealous and concludes after a survey of the pertinent passages that the translation of 'ēl qannā' with »a jealous God« misrepresents the intended meaning of the texts. The author argues instead for a more appropriate translation with »an impassioned God«. Such a translation mirrors more closely God's constant wooing of his people and touches upon modern theological and pastoral sensibilities as well.